Enhancing Intra-African Investment: An Examination of the Role of the African Continental Free Trade Area (AFCFTA) - Ouedraogo, F. K. S. (University of Ghana, 2024)
The African Continental Free Trade Area (AfCFTA) is a transformative initiative aimed at fostering economic integration across Africa by reducing trade and investment barriers. This dissertation examines the role of the AfCFTA in enhancing intra-African investment, focusing on the major barriers to investment, the agreement's potential to address these challenges, and the complementary strategies required to maximize its impact. The study employs a qualitative research approach, utilizing primary data collected through interviews with key stakeholders, including officials from the Ghana Investment Promotion Centre (GIPC), the Ministry of Trade and Industry (MOTI), and the AfCFTA Coordinating Council. The findings reveal that intra African investment is constrained by regulatory inconsistencies, inadequate infrastructure, market fragmentation, and limited access to finance. However, the AfCFTA’s provisions for investment facilitation, regulatory harmonization, and the creation of a single African market offer significant opportunities to mitigate these barriers. Furthermore, the study highlights the importance of complementary policy reforms at national and regional levels, including tax incentives, streamlined investment processes, and alignment of regional economic community (REC) policies with AfCFTA objectives. The private sector's proactive strategies, such as joint ventures and cross-border partnerships, are also identified as critical to leveraging the AfCFTA’s benefits. The dissertation concludes that while the AfCFTA holds immense potential to boost intra-African investment, its success depends on coordinated efforts among governments, RECs, and private sector actors. Recommendations include harmonizing regulatory frameworks, investing in infrastructure, supporting SMEs, and enhancing policy coordination across member states. By addressing these challenges, the AfCFTA can serve as a catalyst for sustainable economic growth and development across Africa
MA. International Affairs
Keywords: African Continental Free Trade Area (AfCFTA); intra-African investment; Ghana Investment Promotion Centre (GIPC); economic integration